2007
DOI: 10.1128/jvi.02712-06
|View full text |Cite
|
Sign up to set email alerts
|

The Fitness Cost of Mutations Associated with Human Immunodeficiency Virus Type 1 Drug Resistance Is Modulated by Mutational Interactions

Abstract: It is generally accepted that the fitness cost of resistance mutations plays a role in the persistence of transmitted drug-resistant human immunodeficiency virus type 1 and that mutations that confer a high fitness cost are less able to persist in the absence of drug pressure. Here, we show that the fitness cost of reverse transcriptase (RT) mutations can vary within a 72-fold range. We also demonstrate that the fitness cost of M184V and K70R can be decreased or enhanced by other resistance mutations such as D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 24 publications
9
106
3
Order By: Relevance
“…K65R, which confers resistance to the nucleotide analog tenofovir, has been shown to have a reduction in fitness when introduced into laboratory strains, as well as in the context of patient sequences, as measured by the Monogram Biosciences RC assay (35,46,179). Similar findings were also obtained using whole isolates obtained from patients failing tenofovir therapy (175).…”
Section: Mutations Conferring Resistance To Reversesupporting
confidence: 71%
See 3 more Smart Citations
“…K65R, which confers resistance to the nucleotide analog tenofovir, has been shown to have a reduction in fitness when introduced into laboratory strains, as well as in the context of patient sequences, as measured by the Monogram Biosciences RC assay (35,46,179). Similar findings were also obtained using whole isolates obtained from patients failing tenofovir therapy (175).…”
Section: Mutations Conferring Resistance To Reversesupporting
confidence: 71%
“…M184V has a fitness similar to that of the wild type in most T-cell lines where nucleotide concentrations are high (10) but reduced fitness in primary cells that have limited nucleotide pools, such as PBMCs and macrophages (3,10,129). Of note is that there are some more-recent studies that have found reduced fitness of this mutant in cell lines (35,48).…”
Section: Mutations Conferring Resistance To Reversementioning
confidence: 99%
See 2 more Smart Citations
“…The NNRTI class has a low resistance barrier (single mutations may cause a significant decrease in drug susceptibility) and NNRTI based highly active treatment combinations are a popular initial regimens in the country as well in the WHO treatment program. The presence of K103N, the most common DRM observed, may be partially explained by the low impact on the viral fitness of this mutation, a fact that favours its persistence (Cong et al 2007). Another mutation associated with NNRTI, at codon P236, probably represents a natural polymorphism, unrelated to primary resistance secondary to transmission, as Delavirdine is rarely used in this area and Efavirenz and Nevirapine do not select for this mutation.…”
Section: Discussionmentioning
confidence: 99%